Tauhid dalam Pemikiran Ismail Raji Al-Faruqi dan Implementasinya dalam Humanisme Islam - Eva Sumasniar; Alfi Julizun Azwar; Yen Fikri Rani (JIA (Jurnal Ilmu Agama), 2020)
This study aims to find out that Tauhid is one of the main teachings of Islam that was revealed by God to the prophet Muhammad SAW and it is even common to say that the teachings of Tauhid are the basis of all truth, and are root of Islam. The purpose of this research is first, to explain Tauhid according to Ismail Raji al-Faruqi. Second, to explain Islamic Humanism according to Ismail Raji al-Faruqi. Third, to explain the relationship between the implementation of monotheism and Islamic humanism according to Ismail Raji al-Faruqi. This research is a qualitative research, where all the data comes from the literature. Therefore, this research will be conducted through the necessary data collection methods by searching for information and written materials. Data collection techniques in this study focused on tracing and reviewing documents or written data sources, both primary and secondary data. The data analysis technique uses the interpretation method. That is an activity to interpret an object of understanding into a form of understanding the researcher himself. From the result of this analysis, it is concluded that the implementation between Tauhid and Islamic Humanism is that God has applied humans to worship and serve Him, and where God did not create humans to play game or in vain God has granted him the five senses, reason, understanding, make man very perfect even to the point of blowing His spirit into him with the aim of preparing to carry out his big task where that big task is the reason that man was created and God is the final goal in man himself.